Mitochondria targeted self-assembled ratiometric fluorescent nanoprobes for pH imaging in living cells. Issue 15 (1st April 2019) - Feng, Zhenzhen; Ma, Yanyun; Li, Bingjie; He, Leiliang; Wang, Qing; Huang, Jin; Liu, Jianbo; Yang, Xiaohai; Wang, Kemin
Abstract : Ratiometric fluorescence imaging of mitochondrial pH based on self-assembled fluorescent nanoprobes. Abstract : Acatastatic pH values of organelles are associated with cell dysfunction and various diseases, which may increase the risk of diabetes, obesity, cancer, Alzheimer's disease and so on. Thus, in situ monitoring of the pH of organelles is extremely essential. Herein, we designed ratiometric fluorescent nanoprobes based on self-assembly for imaging of mitochondrial pH in living cells. The nanoprobes consisted of three parts: (1) a β-cyclodextrin polymer (β-CDP) acted as the backbone of the nanoprobes; (2) two lipophilic dyes acted as the pH sensitive unit and reference unit, i.e. adamantane-labeled fluorescein (Ad-F) and adamantane-labeled rhodamine (Ad-R); (3) adamantane-labeled triphenylphosphonium (Ad-TPP) acted as the mitochondrial targeting unit. Confocal microscopy images proved that the nanoprobes have been successfully applied to monitor intracellular pH in the range of pH 4.0–8.0. Moreover, as evidenced by co-localization imaging, the nanoprobes also showed good ability to target mitochondria (Pearson correlation coefficient was 0.88). Additionally, the nanoprobes showed low toxicity, excellent pH reversibility, and flexibility of construction, and have the potential to monitor pH of other organelles if different targeting units are conjugated. Our strategy is expected to provide new tools for pH monitoring in specific organelles and diagnosis of pH related diseases.